Cytotoxic and Apoptogenic Sesquiterpenoids from the Petroleum Ether Extract of Artemisia aucheri Aerial Parts - Hosseinzadeh, Leila (Iran J Pharm Res, 2019)
Different types of Artemisia aucheri extracts were reported to have various biological activities including a cytotoxic effect on some cancer cell lines. We investigated the antiproliferative activity of isolated sesquiterpenoids from petroleum ether extract of Artemisia aucheri (A. aucheri) aerial parts on SK-N-MC, MCF-7, and A2780 cell lines. Phytochemicals from the petroleum ether cold macerated extract were isolated using normal phase vacuum liquid chromatography and high pressure liquid chromatography (VLC and HPLC) and the structures of the components were determined by spectroscopic means. Cell viability was determined by 3-(4,5- dimethylthiazol-2yl)-2,5-diphenyltetrazolium bromide assay. Activation of caspases-3 and -9 was evaluated using a spectrophotometer. Mitochondrial membrane potential (MMP) was measured using rhodamine 123 fluorescent dye. Two tetrahydrofuran- type sesquiterpenoids, hydroperoxide of davanone (1) and hydroxydavanone (2) were isolated and characterized. Between these compounds, compound 1 exhibited more potent activity against the MCF-7, SK-N-MC and A2780 cell lines with IC(50) values of 8.45 ± 0.81 µg/mL, 9.60 ± 1.32 µg/mL and 10.9 ± 2.03 µg/mL in A2780, MCF-7 and SK-N-MC cells, respectively. Compound 1 inhibited the growth of human cancer cells by induction of apoptosis. To the best of our knowledge, this is the first comprehensive study on cytotoxic and apoptotic mechanism of two davanone derivatives isolated from A. aucheri in human cancer cells. Overall, our data suggest that hydroperoxide of davanone (1) should be further studied in-vivo as a potential antitumor agent.